Integrated production optimization of an oil field based on constructing of a proxy model using DOE methods - Mahyar Rajabi-Kochi; Ehsan Khamehchi (Journal of Petroleum Exploration and Production Technology, 2020)
Abstract An integrated model of the PUNQ-S3 reservoir in the North Sea was constructed. Then, 16 parameters with the highest impact on target functions were selected for sensitivity analysis. The sensitivity analysis was based on the two-level Plackett–Burman design of experimental method. Finally, seven variables with the highest impact on the target functions were selected. Net present value, cumulative oil production, and cumulative water production were three target functions. The proxy model was constructed using the three-level Box–Behnken experimental design for each of the three target functions, taking into account the effect of the variable’s interactions on each other. Then the compliance and predictivity of the proxy model for each target function were validated according to the decision variables. In the end, multiobjective optimization was conducted with the aim of maximizing net present value and cumulative oil production and minimizing cumulative water production using a parameter called composite desirability.